2009
DOI: 10.1007/s00167-009-0935-5
|View full text |Cite
|
Sign up to set email alerts
|

The arthroscopic deepening trochleoplasty

Abstract: Since a dysplastic trochlea has been identified as the main pathomorphology in recurrent patellofemoral instability, trochleoplasty became a surgical solution in some of these cases. However, in comparison to other surgical procedures stabilizing the patellofemoral joint, trochleoplasty is a major operation with an arthrotomy, and associated typical risks of open surgery such as arthrofibrosis. Therefore, we developed a technique to perform an arthroscopic deepening trochleoplasty via suprapatellar portals usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 19 publications
0
41
0
3
Order By: Relevance
“…The technique has been found to be reproducible and safe, without serious complications, but should only be performed by experienced surgeons. The postoperative level of pain and the length of recovery seem to be less compared with the open method, 25 though no randomized studies have yet compared the 2 methods. Clinically, the ADT results in significant improvements in postoperative Kujala and KOOS scores, and also provides stable patellae with no cases of arthrofibrosis having been reported.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The technique has been found to be reproducible and safe, without serious complications, but should only be performed by experienced surgeons. The postoperative level of pain and the length of recovery seem to be less compared with the open method, 25 though no randomized studies have yet compared the 2 methods. Clinically, the ADT results in significant improvements in postoperative Kujala and KOOS scores, and also provides stable patellae with no cases of arthrofibrosis having been reported.…”
Section: Resultsmentioning
confidence: 86%
“…Since the original article was published in 2010, the procedure has undergone a minor change, with the omission of the superior lateral cannula, which was found to be superfluous. 25 In the primary study, a median visual analog scale(VAS) pain score of 3 was observed 24 hours after the operation, and this equalized the level of pain scores from MPFL reconstructions alone. Based on these findings, we found the combined ADT and MPFL procedures to be suitable for 1-day surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of trochlear dysplasia can be addressed with a trochlear groove deepening trochleoplasty procedure, as described by Dejour (Lyon's procedure) [66], or its variants which led to good clinical outcomes in the literature [41,67,68,69,70,71,72]. Long-term studies on the effectiveness of trochleoplasty are scarce.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Working through suprapatellar portals, they elevated a thin osteochondral trochlear flap, undermined the cancellous bone behind it with the use of a shaver, and fixed the flap with the use of anchors and absorbable sutures. 31 When an open surgery is not required by associated procedures, the arthroscopy procedure is appealing.…”
Section: Introduction and Historical Overviewmentioning
confidence: 99%